ANALISIS KINERJA KEUANGAN PEMERINTAH PROVINSI JAMBI PADA LAPORAN KEUANGAN PEMERINTAH DAERAH SEBELUM DAN SESUDAH DITERAPKANNYA BASIS AKRUAL TAHUN 2014 - 2015 - Fathiyah Fathiyah; Masnun Masnun (Ekonomis: Journal of Economics and Business, 2017)
The purpose of this study is to analyze the financial performance of Jambi Provincial Government in the regional financial statements before and after the implementation of accrual basis in 2014 and 2015. The result of the research shows that the financial performance of Jambi Provincial Government as measured by liquidity ratio, solvency ratio and leverage ratio are still in good category and within safe limits because value of all the ratio is above industry standard, although in 2015 there is a decrease in all value ratio because in that year the Jambi Provincial Government has applied the accrual basis in presenting the financial statements so that there is a decrease in the asset post that is in the post of current assets due to allowance for receivables and on the post of fixed assets due to depreciation of fixed assets. Decrease in asset value automatically leads to a decrease in its financial performance.Keywords : financial performance, financial ratio, accrual basis